Family Burden for the Caregivers of People with Mental Disorders: A Systematic Review - Aplonia Nenobais; Atika Jatimi; Muh Jufriyanto (Universitas Airlangga, 2019)
Introduction: The main caregivers of people with mental disorders are their family members. Families as the caregivers of people with mental disorders is associated with a significant burden. This systematic review aims to identify and summarize the main focus based on the scientific evidence about family burden as the caregivers of people with mental disorders.Methods: The databases used were Scopus, Science Direct and Sage Journal with the keywords ‘burden’, ‘family’, ‘caregiver’, ‘mental’, ‘health’, ‘illness’, ‘disorder’ and they were limited to 2014 – 2018 from within nursing and health science journals. One hundred and four full text articles were reviewed. The 14 articles that fulfilled the inclusion criteria were analyzed using narrative synthesis followed the Joanna Briggs Methodology model for the Qualitative Systematic Review to find the main themes of each article.Results: Seven main themes were found to be related to family burden as the caregivers of a family member with mental disorders. The 7 themes were knowledge, emotional burden, physical burden, medication, financial burden, social burden, health services and government support.Conclusion: The findings suggest that the family burden on the caregivers was diverse and that this has an effect on the ability of the family to care for patients with mental disorders. Family burden has become an important indicator for the provision of mental health services.